PERLINDUNGAN HUKUM TERHADAP PEMBELI BERITIKAD BAIK PADA JUAL BELI HAK ATAS TANAH - Amin, Muhammad; Septyanun, Nurjannah; Erwin, Yulias (LPPM STIH Awang Long, 2023)
This research aims to analyze the legal considerations of judges in legal protection for buyers in good faith when buying and selling land rights which are confirmed by court decisions and the Supreme Court decision. The research method used in this research is a normative juridical approach research method, the author summarizes the Selong District Court Decision, the Mataram High Court Decision and the Supreme Court Decision. Based on the results of the research, it shows that the meaning of good faith is a buyer who buys and sells land using valid procedures/procedures and documents as determined by statutory regulations and is careful by examining matters relating to the land object being agreed upon. Legal protection for buyers with good intentions is that the Panel of Judges decides the validity of the sale and purchase carried out by the buyer. Before carrying out a land sale and purchase transaction, every prospective buyer must check the land they want to buy to ensure that there are no disputes regarding the object, ensure that the seller is the original owner of the object, it would be better for the House of Representatives to make clear regulations regarding the criteria for buyers in good faith. and firm.